A review of Neospora caninum in water buffalo ( Bubalus bubalis ) - Reichel, Michael P. (2015)
A number of countries in the world have reported infections with Neospora caninum in water buffalo (Bubalus bubalis), from Africa to Asia, Europe and South America and recently Australia. In general, clinical manifestations (such as abortion) seem infrequent, which has raised the prospect that buffalo may be inherently resistant to clinical effects from N. caninum infection, yet worldwide the seroprevalence of N. caninum infection (as a measure of exposure determined by the detection of antibody) in buffalo is approximately 48%. This reported seroprevalence is approximately three or four times higher than that reported from the world?s cattle populations, which have collective seroprevalence rates of 16.1% for dairy cattle and 11.5% for beef cattle. However, there is a lack of standardisation in seroprevalence studies and some studies may well under-estimate the true level of infection. Epidemiologic evidence supports post-natal transmission, and in utero transmission has also been demonstrated. The causes for water buffalo to have markedly higher seroprevalence but apparently lower neosporosis abortion rates than cattle warrant further investigation.